A fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment and preparation method thereof

By using fluorinated ZIF-67/graphene composite catalyst in coal chemical wastewater treatment, the problem of metal leaching of the catalyst under harsh conditions is solved, and efficient degradation of pollutants difficult to degrade in coal chemical wastewater is achieved, and good stability and mechanical properties are achieved.

CN119746930APending Publication Date: 2025-04-04南京宇清环境科技有限公司 +1

Patent Information

Application Number
CN202411902206.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when treating coal chemical wastewater, the catalyst is prone to metal leaching under harsh conditions, resulting in secondary pollution of the water body and poor long-term application of complex wastewater.

Method used

Porous graphene is used as a support to support fluorinated ZIF-67, and fluorinated ZIF-67 is formed by introducing 2-trifluoromethylimidazole into ZIF-67, and uniformly growing it on the surface of the graphene support through in-situ preparation method to prepare a fluorinated ZIF-67/graphene composite catalyst.

Benefits of technology

This catalyst is not easily eroded during water treatment, has high efficiency degradation ability, has significant effects on pollutants such as phenolic compounds and oils that are difficult to biodegrade. It also has good mechanical properties and durability, reducing the risk of metal leaching.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746930A_ABST
    Figure CN119746930A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of water treatment technology, and relates to a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment and a preparation method thereof. The catalyst uses porous graphene as a carrier to load fluorinated ZIF-67. First, 2-trifluoromethylimidazole is introduced into ZIF-67 to prepare fluorinated ZIF-67, and an in-situ preparation method is used to make it grow evenly on the surface of a porous graphene carrier to obtain a fluorinated ZIF-67 / graphene composite catalyst. 2-trifluoromethylimidazole modification can improve the hydrophobicity of the catalyst, making it less susceptible to erosion during water treatment; The porous structure of graphene provides a larger specific surface area, increases the number of active sites of the catalyst, prevents nanoparticles from agglomerating, and improves its mechanical strength. The catalyst has the ability to highly degrade organic pollutants, is suitable for treating pollutants such as phenols and greases that are difficult to biodegrade in coal chemical wastewater, and has broad market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and specifically relates to a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater and a preparation method thereof. Background Art

[0002] With the rapid development of the coal chemical industry, the discharge of coal chemical wastewater has increased significantly. Compared with other types of industrial wastewater, coal chemical wastewater contains higher concentrations of pollutants such as phenols and oils that are difficult to degrade. Traditional treatment methods, such as adsorption and membrane separation technology, have limitations; the adsorbent used in the adsorption method has limited adsorption capacity, is difficult to recover and regenerate, and has high costs; the membrane treatment method faces problems such as high energy consumption, large initial investment, and high maintenance and replacement costs of membrane components. In contrast, advanced oxidation technology has received widespread attention due to its low energy consumption and ability to efficiently degrade organic matter in coal chemical wastewater, especially ozone catalytic oxidation, which has become the preferred choice for treating wastewater due to its fast reaction rate, easy-to-prepare catalysts, and environmental friendliness.

[0003] A Chinese patent application with publication number CN 108579755 A discloses a wastewater treatment catalyst prepared by impregnation and calcination. The catalyst uses doped manganese, cobalt, nickel and potassium elements to improve the efficiency of ozone catalytic oxidation, effectively degrade pollutants in organic wastewater, and show good reusability. However, under harsh conditions, the catalyst will experience metal leaching, which will cause secondary pollution to the water body. A Chinese patent application with publication number CN 117101660A discloses a porous polyhedral Fe-Co bimetallic catalyst prepared by a hydrothermal method and high-temperature calcination; the catalyst is rich in oxygen vacancies, can efficiently degrade organic pollutants in wastewater, and has good catalytic performance, but the long-term application effect on complex wastewater needs further study. A Chinese patent application with publication number CN 115888738 A discloses a method for preparing a copper / cerium bimetallic oxide ozone catalyst by a solvothermal method combined with a high-temperature calcination technique; the catalyst exhibits high catalytic activity and can effectively treat a variety of high-concentration organic wastewaters, but the bimetallic atom strategy will interfere with the lattice structure of the original framework and affect the stability of the material itself.

[0004] Based on the above problems, developing a catalyst with high catalytic activity, excellent stability and low metal leaching risk remains an urgent problem to be solved in this field. Summary of the invention

[0005] The present invention aims to provide a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater and a preparation method thereof. The catalyst uses porous graphene as a carrier to load fluorinated ZIF-67. First, 2-trifluoromethylimidazole is introduced into ZIF-67 to form fluorinated ZIF-67, and an in-situ preparation method is used to uniformly grow it on the surface of the porous graphene carrier to obtain a fluorinated ZIF-67 / graphene composite catalyst. 2-trifluoromethylimidazole modification improves the hydrophobicity of the catalyst, making it less susceptible to erosion during water treatment; the porous structure of graphene provides a larger specific surface area, increases the number of active sites of the catalyst, and improves its mechanical strength. The catalyst has a high efficiency in degrading organic pollutants, is suitable for treating pollutants such as phenolic compounds and greases that are difficult to biodegrade in coal chemical wastewater, and has broad market prospects.

[0006] To achieve the above-mentioned purpose, the present invention provides a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment, wherein the catalyst uses porous graphene as a carrier to load fluorinated ZIF-67; 2-trifluoromethylimidazole is introduced into ZIF-67 to form fluorinated ZIF-67, and an in-situ preparation method is adopted to uniformly grow it on the surface of the porous graphene carrier to obtain a fluorinated ZIF-67 / graphene composite catalyst.

[0007] The present invention also provides a method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater, comprising:

[0008] Maleic acid and sodium carbonate are dissolved in a solvent, ultrasonically treated, and dried; the dried solid is ground into powder, transferred to a tube furnace, programmedly heated under argon protection, calcined, and the product is washed and dried to obtain porous graphene;

[0009] Cobalt nitrate hexahydrate is dissolved in a solvent, stirred evenly, added to porous graphene, and subjected to ultrasonic treatment to obtain solution A; 2-methylimidazole and 2-trifluoromethylimidazole are dissolved in an organic solvent to obtain solution B; solution B is slowly added dropwise to solution A, allowed to stand, centrifuged, washed, and dried to obtain a composite catalyst.

[0010] Preferably, the mass ratio of the solvent, maleic acid and sodium carbonate is 1:(0.068-0.087):(0.27-0.37); the solvent is any one or more of deionized water, methanol and anhydrous ethanol; and the washing solution is anhydrous ethanol and deionized water.

[0011] Preferably, the programmed heating rate is 5°C / min; the argon flow rate is 50 mL / min.

[0012] Preferably, the calcination temperature is 600-700° C., and the calcination time is 2-3 hours.

[0013] Preferably, the mass ratio of the solvent, cobalt nitrate hexahydrate and graphene is 1:(0.012-0.015):(0.002); the solvent is any one or more of ultrapure water, acetone, anhydrous ethanol and methanol.

[0014] Preferably, the mass ratio of the organic solvent, 2-methylimidazole and 2-trifluoromethylimidazole is 1:(0.012-0.013):(0.003-0.005); the organic solvent is any one or more of methanol, anhydrous ethanol and isopropanol.

[0015] Preferably, the volume ratio of solution A to solution B is 1:1.

[0016] Preferably, the standing time is 20 to 24 hours; and the washing solution is methanol and deionized water.

[0017] Preferably, the drying temperature is 50-60° C., and the drying time is 10-12 hours.

[0018] Preferably, the ultrasonic treatment time is 5 to 10 min, and the stirring time is 5 to 10 min.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] (1) The present invention uses 2-trifluoromethylimidazole to modify ZIF-67 to obtain fluorinated ZIF-67. The fluorination process is the most effective method to improve the hydrophobicity and water stability of the material. The corrosion resistance and service life of fluorinated ZIF-67 in water are significantly improved, and it can also promote the generation of strong oxidizing free radicals.

[0021] (2) The present invention uses porous graphene as a carrier to load fluorinated ZIL-67. Porous graphene provides a high specific surface area and abundant adsorption sites, enhances the adsorption capacity of fluorinated ZIF-67, improves the catalytic activity, and can effectively prevent the agglomeration of nanoparticles, thereby enhancing the mechanical properties and durability of the catalyst.

[0022] (3) The present invention synthesizes porous graphene through a one-step carbonization process, avoiding the use of harmful etching agents, thereby reducing the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the COD degradation efficiency of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 2 in coal chemical wastewater.

[0024] Figure 2 It is the chromaticity removal rate of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 2 for coal chemical wastewater. DETAILED DESCRIPTION

[0025] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0026] Example 1

[0027] A method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater comprises the following steps:

[0028] (1) Accurately weigh 1.161 g of maleic acid and 5.299 g of sodium carbonate, dissolve in 20 mL of deionized water, ultrasonically treat for 5 to 10 min, dry at 50 to 60 ° C for 10 to 12 h, take out the dried solid and grind it thoroughly, move the ground powder into a tube furnace, and calcine it at 600 to 700 ° C at a rate of 5 ° C / min for 2 to 3 h in an argon gas flow rate of 50 mL / min. The product is washed with anhydrous ethanol and deionized water respectively, and dried in a vacuum at 50 to 60 ° C for 10 to 12 h to obtain porous graphene.

[0029] (2) Accurately weigh 0.436 g of cobalt nitrate hexahydrate and dissolve it in 50 mL of ultrapure water. Stir and mix well for 10 min. Add 0.1 g of porous graphene and perform ultrasonic treatment to obtain solution A. Accurately weigh 0.517 g of 2-methylimidazole and 0.105 g of 2-trifluoromethylimidazole and dissolve them in 50 mL of methanol. Perform ultrasonic treatment for 5 to 10 min to obtain solution B.

[0030] (3) Solution B is slowly added dropwise to solution A while stirring, and the mixture is allowed to stand for 20 to 24 hours before centrifugation. The precipitate is washed with methanol and deionized water respectively, and vacuum dried at 50 to 60° C. for 10 to 12 hours to obtain a composite catalyst.

[0031] Example 2

[0032] A method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater comprises the following steps:

[0033] (1) Accurately weigh 1.741 g of maleic acid and 6.359 g of sodium carbonate, dissolve in 20 mL of deionized water, ultrasonicate for 5 to 10 min, dry at 50 to 60 ° C for 10 to 12 h, take out the dried solid and grind it thoroughly, move the ground powder into a tube furnace, and calcine it at 600 to 700 ° C at a rate of 5 ° C / min for 2 to 3 h in an argon gas atmosphere with a flow rate of 50 mL / min. The product is washed with anhydrous ethanol and deionized water, respectively, and dried at 50 to 60 ° C in a vacuum oven for 10 to 12 h to obtain porous graphene.

[0034] (2) Accurately weigh 0.582 g of cobalt nitrate hexahydrate, dissolve it in 50 mL of ultrapure water, stir for 5 to 10 min to mix evenly, add 0.1 g of porous graphene, and ultrasonically treat for 5 to 10 min to obtain solution A; accurately weigh 0.488 g of 2-methylimidazole and 0.143 g of 2-trifluoromethylimidazole, dissolve them in 50 mL of methanol, stir for 5 to 10 min, and ultrasonically treat for 5 to 10 min to obtain solution B.

[0035] (3) Solution B is slowly added dropwise to solution A while stirring, and the mixture is allowed to stand for 20 to 24 hours before centrifugation. The precipitate is washed with methanol and deionized water respectively, and then dried in a vacuum at 50 to 60° C. to obtain a composite catalyst.

[0036] Example 3

[0037] A method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater comprises the following steps:

[0038] (1) Accurately weigh 2.321 g of maleic acid and 7.419 g of sodium carbonate, dissolve in 20 mL of deionized water, ultrasonically treat for 5 to 10 min, dry at 50 to 60 ° C for 10 to 12 h, take out the dried solid and grind it thoroughly, move the ground powder into a tube furnace, and calcine it at 600 to 700 ° C at a rate of 5 ° C / min for 2 to 3 h in an argon gas flow rate of 50 mL / min. The product is washed with anhydrous ethanol and deionized water, respectively, and dried in a vacuum at 50 to 60 ° C for 10 to 12 h to obtain porous graphene.

[0039] (2) Accurately weigh 0.727 g of cobalt nitrate hexahydrate, dissolve it in 50 mL of ultrapure water, stir for 5 to 10 min, add 0.1 g of porous graphene, and ultrasonically treat for 5 to 10 min to obtain solution A; accurately weigh 0.460 g of 2-methylimidazole and 0.191 g of 2-trifluoromethylimidazole, dissolve them in 50 mL of methanol, stir for 5 to 10 min, and ultrasonically treat for 5 to 10 min to obtain solution B.

[0040] (3) Solution B is slowly added dropwise to solution A while stirring, and the mixture is allowed to stand for 20 to 24 hours before centrifugation. The precipitate is washed with methanol and deionized water respectively, and vacuum dried at 50 to 60° C. for 10 to 10 hours to obtain a composite catalyst.

[0041] Comparative Example 1

[0042] A method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater, which is different from Example 3 in that 2-trifluoromethylimidazole is not added in step (2).

[0043] Comparative Example 2

[0044] A method for preparing a fluorinated ZIF-67 / graphene composite catalyst for treating coal chemical wastewater, which is different from Example 3 in that porous graphene is not added in step (3).

[0045] Performance Testing:

[0046] (1) Test device: The device includes an ozone generator, a gas flow meter, a columnar glass reactor, and an exhaust gas absorption device. The ozone generator is connected to the gas flow meter through a pipeline, which can accurately control the flow rate of ozone gas entering the reactor. The gas outlet of the gas flow meter is connected to the air inlet of the reactor through a pipeline, and a stirring device is installed inside to promote the thorough mixing of wastewater, ozone and catalyst. The reactor is equipped with multiple sampling ports for convenient sampling at different time points to monitor the progress of the reaction. The exhaust port of the reactor is connected to the exhaust gas treatment device through a pipeline to treat unreacted ozone.

[0047] (2) Test method: Take 10g of the composite catalyst prepared in Examples 1 to 3 and Comparative Examples 1 to 2, and evenly load it into the bottom of a 1L glass reactor. Take 1L of coal chemical wastewater sample, start the ozone generator, set the ozone concentration to 50mg / L, the flow rate to 0.5L / min, pass ozone into the reactor, the reaction time is 1h, take samples at intervals for analysis, use high performance liquid chromatography to detect phenol concentration, use a water quality analyzer to analyze the COD concentration at each time point, and use a spectrophotometer to measure the color. The test results are shown in Table 1, Table 2, Figure 1 , Figure 2 shown.

[0048] according to Figure 1 As shown, the efficiency of the composite catalysts prepared in Examples 1 to 3 in degrading COD in coal industrial wastewater is significantly higher than that of the composite catalysts prepared in Comparative Examples 1 to 2. The effect of Example 3 is the most significant, with a COD degradation efficiency of more than 80% in 30 minutes and a degradation efficiency of more than 95% in 1 hour.

[0049] according to Figure 2 As shown, the composite catalysts prepared in Examples 1 to 3 exhibit excellent performance in reducing the chromaticity of coal industry wastewater, and the chromaticity removal efficiency is higher than that of the composite catalysts prepared in Comparative Examples 1 to 2. Among them, Example 3 has the best effect, with a chromaticity removal rate of more than 80% in 40 minutes and more than 90% in 1 hour.

[0050] Table 1 Catalytic performance parameters of composite catalyst

[0051]

[0052] Table 2 Parameters of phenol removal rate of composite catalyst

[0053]

[0054] According to the data in Table 1 and Table 2, the catalytic degradation efficiency of phenol and COD prepared by the composite catalysts of Examples 1 to 3 is higher than that of the comparative examples, and the effect of Example 3 is significantly higher than that of Examples 1 and 2. Compared with Example 3, 2-trifluoromethylimidazole was not added in Comparative Example 1, and the catalytic effect of the catalyst was significantly reduced. The main reason is that the catalyst lacks fluorine atom modification, which weakens its hydrophobicity and water stability, and weakens its free radical generation ability, thereby reducing the efficiency of catalytic degradation of organic pollutants. In Comparative Example 2, no porous graphene carrier was added, and the catalytic efficiency was also significantly lower than that of Example 3. The reason is that there is a lack of porous graphene carrier in the catalyst system, there is no large specific surface area, and the ZIF-67 nanoparticles are agglomerated and unevenly distributed, thereby affecting the catalytic effect of the catalyst.

[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment, characterized in that: The catalyst uses porous graphene as a carrier and loads fluorinated ZIF-67; 2-trifluoromethylimidazole is introduced into ZIF-67 to prepare fluorinated ZIF-67, and an in-situ preparation method is used to uniformly grow it on the surface of the porous graphene carrier to obtain a fluorinated ZIF-67 / graphene composite catalyst.

2. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 1, characterized in that: include: Maleic acid and sodium carbonate are dissolved in a solvent, ultrasonically treated, and dried. The dried solid is ground into powder, transferred to a tube furnace, programmedly heated under argon protection, calcined, and the product is washed and dried to obtain porous graphene; Cobalt nitrate hexahydrate is dissolved in a solvent, stirred evenly, added to porous graphene, and subjected to ultrasonic treatment to obtain solution A. 2-Methylimidazole and 2-trifluoromethylimidazole are dissolved in an organic solvent to obtain solution B. Solution B is added dropwise to solution A, allowed to stand, centrifuged, washed, and dried to obtain a composite catalyst.

3. According to the preparation method of a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, the mass ratio of the solvent, maleic acid and sodium carbonate is 1: (0.068~0.087): (0.27~0.37); the solvent is any one or more of deionized water, methanol and anhydrous ethanol.

4. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The calcination temperature is 600-700° C., and the calcination time is 2-3 hours; the programmed heating rate is 5° C. / min, and the argon gas flow rate is 50 mL / min; and the washing solutions are anhydrous ethanol and deionized water, respectively.

5. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The mass ratio of the solvent, cobalt nitrate hexahydrate and graphene is 1:(0.012-0.015):(0.002); the solvent is any one or more of ultrapure water, acetone, anhydrous ethanol and methanol.

6. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The mass ratio of the organic solvent, 2-methylimidazole and 2-trifluoromethylimidazole is 1:(0.012-0.013):(0.003-0.005); the organic solvent is any one or more of methanol, anhydrous ethanol and isopropanol.

7. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The volume ratio of solution A to solution B is 1:

1.

8. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The standing time is 20 to 24 hours; the washing solutions are methanol and deionized water respectively.

9. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The drying temperature is 50-60° C. and the drying time is 10-12 hours.

10. The method for preparing a fluorinated ZIF-67 / graphene composite catalyst for coal chemical wastewater treatment according to claim 2, characterized in that: The stirring time is 5 to 10 minutes; the ultrasonic treatment time is 5 to 10 minutes.

Citation Information

Patent Citations

  • Waste water treatment catalyst and application thereof

    CN108579755A

  • Preparation method and application of copper-cerium bimetallic oxide ozone catalyst

    CN115888738A

  • Preparation method of porous polyhedral Fe-Co bimetallic wastewater treatment catalyst

    CN117101660A

Cited By

  • Fluorine functionalized composite ceramic membrane as well as preparation method and application thereof

    CN120394095A

  • A fluorine-functionalized composite ceramic membrane and its preparation method and application

    CN120394095B